Cultural Linguistics as an investigative framework for paremiology: comparing time in English and Persian. (18th November 2016) - Dabbagh, Ali
Abstract : This paper introduces Cultural Linguistics to the analysis of proverbs using the three analytical tools of cultural metaphor, cultural schema, and cultural category, which are collectively referred to as cultural conceptualisations . To substantiate this, the paper reports on a study in which English and Persian cross‐culturally equivalent proverbs related to the concept of time were scrutinised using this analytical framework. The results revealed a number of similar and different images of time in the proverbs investigated metaphorically and schematically but not categorically. The paper concludes that such analysis can assist paremiologists to deepen their understanding of proverbs especially in comparative paremiology from different languages with distinct cultural backgrounds.